Carbon Nanotubes and Metalloporphyrins and Metallophthalocyanines-Based Materials for Electroanalysis - Zagal-Moya, J; Zagal-Moya, J; Santander-Nelli, M; Santander-Nelli, M (World Scientific Publishing Co. Pte Ltd, 2012)
We discuss here the state of the art on hybrid materials made from single (SWCNT) or multi (MWCNT) walled carbon nanotubes and MN4 complexes such as metalloporphyrins and metallophthalocyanines. The hybrid materials have been characterized by several methods such as cyclic voltammetry (CV), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM) and scanning electrochemical microscropy (SECM). The materials are employed for electrocatalysis of reactions such as oxygen and hydrogen peroxide reduction, nitric oxide oxidation, oxidation of thiols and other pollutants. Copyright © 2012 World Scientific Publishing Company.